Magnetic Resonance Relaxometry at Low and Ultra low Fields - Volegov, P. (2010)
Nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) are ubiquitous tools in science and medicine. NMR provides powerful probes of local and macromolecular chemical structure and dynamics. Recently it has become possible and practical to perform MR at very low fields (from 1 μT to 1 mT), the so-called ultra-low field (ULF) regime. Pulsed pre-polarizing fields greatly enhance the signal strength and allow flexibility in signal acquisition sequences. Improvements in SQUID sensor technology allow ultra-sensitive detection in a pulsed field environment. In this regime the proton Larmor frequencies (1 Hz – 100 kHz) of ULF MR overlap (on a time scale of 10 μs to 100 ms) with “slow” molecular dynamic processes such as diffusion, intra-molecular motion, chemical reactions, and biological processes such as protein folding, catalysis and ligand binding. The frequency dependence of relaxation at ultra-low fields may provide a probe for biomolecular dynamics on the millisecond timescale (protein folding and aggregation, conformational motions of enzymes, binding and structural fluctuations of coupled domains in allosteric mechanisms) relevant to host-pathogen interactions, biofuels, and biomediation. Also this resonance-enhanced coupling at ULF can greatly enhance contrast in medical applications of ULF-MRI resulting in better diagnostic techniques. We have developed a number of instruments and techniques to study relaxation vs. frequency at the ULF regime. Details of the techniques and results are presented. Ultra-low field methods are already being applied at LANL in brain imaging, and detection of liquid explosives at airports. However, the potential power of ultra-low field MR remains to be fully exploited.